2019
DOI: 10.1371/journal.pone.0222028
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the balance towards long-term retention in the HIV care cascade: A mixed methods study in southern Mozambique

Abstract: BackgroundThe implementation of quality HIV control programs is crucial for the achievement of the UNAIDS 90-90-90 targets and to motivate people living with HIV (PLWHIV) to link and remain in HIV-care. The aim of this mixed method cross-sectional study was to estimate the linkage and long-term retention in care of PLWHIV and to identify factors potentially interfering along the HIV-care continuum in southern Mozambique.MethodsA home-based semi-structured interview was conducted in 2015 to explore barriers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…Many PLHIV start and stop ART multiple times over the course of their lives, creating what has been termed a “side door” into the cascade through which individuals who have left the system reenter it [ 18 ]. Some people report fear of being treated poorly if they return to care after an absence [ 19 ] and may perceive it as more acceptable to retest and restart ART at a new facility as a “new” patient rather than facing censure from healthcare staff [ 20 , 21 ]. Routinely collected medical records in most settings do not adequately document this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Many PLHIV start and stop ART multiple times over the course of their lives, creating what has been termed a “side door” into the cascade through which individuals who have left the system reenter it [ 18 ]. Some people report fear of being treated poorly if they return to care after an absence [ 19 ] and may perceive it as more acceptable to retest and restart ART at a new facility as a “new” patient rather than facing censure from healthcare staff [ 20 , 21 ]. Routinely collected medical records in most settings do not adequately document this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 Barriers to linkage to care include the fear of dissemination of one’s HIV status, feeling subjectively healthy, migration, health system issues and fears of discrimination. 23 , 24 , 26 …”
Section: Challenges For Achieving 95-95-95 In Esamentioning
confidence: 99%
“…Twenty-eight studies reported on this step [20,23,24,[26][27][28]31,[33][34][35][37][38][39]41,44,45,[47][48][49][50][51][52][53][54][55][56][57][58]: 15 cohort studies, 10 crosssectional and three of mixed design. Twenty-four studies (86%) provided a clear definition of the step (Table 2).…”
Section: Linkage To Pre-art Carementioning
confidence: 99%